The Emperor of Mars - Samphire, Patrick (Samphire, Patrick. Secrets of the dragon tomb series, 2017)
When Edward intercepts a thief, he finds himself drawn into a scheme that threatens the livelihood of everyone on Mars. Unsure who he can trust, Edward hopes he makes the right decisions to protect those he loves and himself.